An Analysis of the Applications Made to a Dermatology Outpatient Clinic by Syrian Migrants Under Temporary Protection: A Retrospective Cross-Sectional Study - Akça, Hanife Merve; Kara, Kevser Tuncer (OrtadogÂŸu Reklam Tanitim Yayincilik Turizm Egitim Insaat Sanayi ve Ticaret A.S., 2022)
Objective: Globally, the number of immigrants is increasing, and they bring with them many health problems. In this study, we examined the applications of Syrian immigrants under temporary protection to a dermatology polyclinic by comparing them with those of local people. Material and Methods: This cross-sectional study was conducted retrospectively. Applications made to the Konya City Hospital Dermatology Polyclinic in March-May 2021 were reviewed. SPSS 22.0 software was used in the analysis of the data. Percentage and median (minimum-maximum) are given in descriptive statistics. Chi-square and Mann-Whitney U tests were used according to the characteristics of the data. A p-value <0.05 was accepted as the significance level. Results: The median age of the patients was 22 (1-81) years. It was determined that 85.2% of those who applied to the polyclinic were residents and 64.0% of these applications were women. When the polyclinic applications were examined, no significant difference was found between the settled population and the Syrian immigrants under temporary protection in terms of age and gender. The results showed that Syrian immigrants under temporary protection visited the dermatology polyclinic proportionately more often than residents. Dermatitis was the most common reason for the visit among Syrian immigrants under temporary protection, residents, and overall, and acne was the second most common complaint. Conclusion: It has been determined that immigrants have more problems in terms of dermatological diseases than the local people. Protective measures should be taken in terms of dermatological diseases, and interventions should be made to improve living conditions. © 2022 OrtadogÃ‚ÂŸu Reklam Tanitim Yayincilik Turizm Egitim Insaat Sanayi ve Ticaret A.S.. All rights reserved.
Keywords: Immigration; dermatitis; acne vulgaris; quality of life